2015
DOI: 10.1111/maec.12338
|View full text |Cite
|
Sign up to set email alerts
|

Different sperm allocation strategies in two populations of the semiterrestrial crab Neohelice granulata (Brachyura, Grapsoidea, Varunidae)

Abstract: Sperm reserves are costly to produce and so the development of different sperm allocation strategies may be advantageous. Knowledge of sperm allocation strategies is important from an evolutionary perspective because they contribute to characterize mating systems. However, population differences in sperm allocation strategies of the same species have rarely been assessed. Here, we studied the male sperm allocation strategies in two different populations of Neohelice granulata in Mar Chiquita Lagoon (MCL) and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 77 publications
(138 reference statements)
1
1
0
Order By: Relevance
“…Besides, recently mated SM did not occupy empty LM burrows (experiment 4) supporting our hypotheses because it demonstrates that not recently mated SM may look for empty LM burrows to occupy with mating purposes in mind. A previous study demonstrated that LM transfer larger ejaculates than SM (Sal Moyano et al 2015), which also support the hypothesis about the Bcheating behavior^of SM. Effective copulation between females and SM inside empty burrows with copulation chambers constructed by LM was demonstrated previously in a field study (Sal Moyano et al 2012a).…”
Section: Discussionsupporting
confidence: 75%
“…Besides, recently mated SM did not occupy empty LM burrows (experiment 4) supporting our hypotheses because it demonstrates that not recently mated SM may look for empty LM burrows to occupy with mating purposes in mind. A previous study demonstrated that LM transfer larger ejaculates than SM (Sal Moyano et al 2015), which also support the hypothesis about the Bcheating behavior^of SM. Effective copulation between females and SM inside empty burrows with copulation chambers constructed by LM was demonstrated previously in a field study (Sal Moyano et al 2012a).…”
Section: Discussionsupporting
confidence: 75%
“…In crab species, variation in ejaculate allocation has been principally associated with male size and operational sex ratio (Jivoff 1997, 2003, Rondeau & Sainte-Marie 2001. The ejaculate allocation strategy can also differ between populations, as has been demonstrated in the semi-terrestrial crab Neohelice granulata (Sal Moyano et al 2015).…”
Section: Introductionmentioning
confidence: 98%